Analisis Faktor-Faktor Yang Mempengaruhi Kemiskinan (Studi Kasus Pada Provinsi Jawa Barat) - Dana Ramadhan; Fazalqo’ni Fazalqo’ni; Deris Desmawan (Universitas Labuhanbatu, 2022)
This study aims to analyze the impact of the Human Development Index, the impact of education, and the impact of open unemployment on the poverty level from 2017 to 2021(West Provincial Case Study).Double regress method.The results showed that the percentage variable open unemployment rate has a positive and significant effect on the level of poverty, while the variable level of education and HDI negative and significant effect on the level of poverty. Results based on the simultaneous Test (Test F) showed that the open unemployment rate, education level and HDI simultaneously affect the level of impoverishment.